ZnT2-Mediated Zinc Import Into Paneth Cell Granules Is Necessary for Coordinated Secretion and Paneth Cell Function in MiceSummary - Abigail B. Podany; Justin Wright; Regina Lamendella; David I. Soybel; Shannon L. Kelleher (Cellular and Molecular Gastroenterology and Hepatology, 2016)
Background & Aims: Defects in Paneth cell (PC) function are associated with microbial dysbiosis and intestinal inflammation. PC granules contain antimicrobial peptides, cytokines, and substantial stores of zinc (Zn). We hypothesized that Zn, transported into the granule through the Zn transporter (ZnT)2, is critical for signature PC functions. Methods: ZnT2 was localized to PC granules using immunofluorescence and sucrose gradient fractionation in wild-type (wt) mice, and consequences of ZnT2 loss were characterized in ZnT2 knockout (ZnT2ko) mice. Terminal ilea were harvested for immunofluorescence, electron microscopy, and fluorescent imaging with the Zn reporter Zinpyr-1. Alterations in fecal microbiota were characterized using 16s ribosomal RNA sequencing. PC degranulation, bacterial translocation, cytokine response to Escherichia coli endotoxin lipopolysaccharide, crypt viability after exposure to the oxidant monochloramine (NH2Cl), and bactericidal activity of luminal contents of terminal ilea against enteropathogenic E coli were assessed. Results: ZnT2 was localized to the membrane of PC granules. In ZnT2ko mice, spontaneous degranulation was observed more frequently than among wt mice. Secretory granules were hypodense with less active lysozyme, and there was evidence of autophagosome accumulation and granule degradation in PCs from ZnT2ko mice. Gut microbiota of ZnT2ko mice were enriched in Bacteroidales S24-7 and relatively depleted of species commonly found in wt mice. Evidence of PC dysfunction in ZnT2ko mice included impaired granule secretion and increased inflammatory response to lipopolysaccharide, less bactericidal activity, and greater susceptibility to cell death from NH2Cl. Conclusions: ZnT2 is critical for Zn import into PC granules, and the inability to import Zn leads to profound defects in PC function and uncoordinated granule secretion. Keywords: Small Intestine, Zinc Transporter, Microbiota